12+38y=512+58y

Combine 38 and y.

12+3y8=512+58y

Combine 58 and y.

12+3y8=512+5y8

Subtract 5y8 from both sides of the equation.

12+3y8-5y8=512

Combine fractions with similar denominators.

12+3y-5y8=512

Subtract 5y from 3y.

12+-2y8=512

Reduce the expression -2y8 by cancelling the common factors.

Factor 2 out of -2y.

12+2(-y)8=512

Factor 2 out of 8.

12+2(-y)2(4)=512

Cancel the common factor.

12+2(-y)2⋅4=512

Rewrite the expression.

12+-y4=512

12+-y4=512

Move the negative in front of the fraction.

12-y4=512

12-y4=512

Subtract 12 from both sides of the equation.

-y4=512-12

To write -12 as a fraction with a common denominator, multiply by 66.

-y4=512-12⋅66

Write each expression with a common denominator of 12, by multiplying each by an appropriate factor of 1.

Multiply 12 and 66.

-y4=512-62⋅6

Multiply 2 by 6.

-y4=512-612

-y4=512-612

Combine the numerators over the common denominator.

-y4=5-612

Subtract 6 from 5.

-y4=-112

Move the negative in front of the fraction.

-y4=-112

-y4=-112

Multiply both sides of the equation by -4.

-4⋅(-y4)=-4⋅(-112)

Simplify -4⋅(-y4).

Cancel the common factor of 4.

Move the leading negative in -y4 into the numerator.

-4⋅-y4=-4⋅(-112)

Factor 4 out of -4.

4(-1)⋅-y4=-4⋅(-112)

Cancel the common factor.

4⋅-1⋅-y4=-4⋅(-112)

Rewrite the expression.

-1⋅(-y)=-4⋅(-112)

-1⋅(-y)=-4⋅(-112)

Multiply.

Multiply -1 by -1.

1⋅y=-4⋅(-112)

Multiply y by 1.

y=-4⋅(-112)

y=-4⋅(-112)

y=-4⋅(-112)

Simplify -4⋅(-112).

Cancel the common factor of 4.

Move the leading negative in -112 into the numerator.

y=-4⋅-112

Factor 4 out of -4.

y=4(-1)⋅-112

Factor 4 out of 12.

y=4⋅-1⋅-14⋅3

Cancel the common factor.

y=4⋅-1⋅-14⋅3

Rewrite the expression.

y=-1⋅-13

y=-1⋅-13

Move the negative in front of the fraction.

y=-1⋅(-13)

Multiply -1(-13).

Multiply -1 by -1.

y=1(13)

Multiply 13 by 1.

y=13

y=13

y=13

y=13

The result can be shown in multiple forms.

Exact Form:

y=13

Decimal Form:

y=0.3‾

Solve for y 1/2+3/8y=5/12+5/8y